Mental health and being smart in Daniel Keyes' Flowers for Algernon - Mehmet Ali Çelikel (Literacy Trek, 2020)
Daniel Keyes' Flowers for Algernon was first published as a short story in The Magazine of Fantasy & Science Fiction in 1959. After the story successfully elicited critical acclaim and brought literary awards to its author, Keyes expanded the story into a novel that was first published in 1966. Daniel Keyes recounts the saddening story of Charlie Gordon, a mentally retarded thirty-two-year-old man, who is chosen by scientists for an experiment that would supposedly improve one's mental capacity in a short time span. The experiment gradually proves to be successful as Charlie's mental health improves. Yet, as Charlie turns unexpectedly very intelligent and cultured, reaching the ability to speak several languages including Latin, he finds out that the experiment he has been through brings a temporary state of mental well-being to the subject who would quickly return to one's initial mental state. This purpose of paper is to discuss the concept of healing and well-being and question whether being well is an ideological or medical concept in terms of madness and civilization from the perspective of Foulcault who sees madness in a certain cultural space in society which the position and definition of "healthy" individuals depend on.